2016
DOI: 10.1371/journal.pone.0150407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melatonin in Epithelial Mesenchymal Transition Markers and Invasive Properties of Breast Cancer Stem Cells of Canine and Human Cell Lines

Abstract: Cancer stem cells (CSCs) have been associated with metastasis and therapeutic resistance and can be generated via epithelial mesenchymal transition (EMT). Some studies suggest that the hormone melatonin acts in CSCs and may participate in the inhibition of the EMT. The objectives of this study were to evaluate the formation of mammospheres from the canine and human breast cancer cell lines, CMT-U229 and MCF-7, and the effects of melatonin treatment on the modulation of stem cell and EMT molecular markers: OCT4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 75 publications
2
54
1
Order By: Relevance
“…Melatonin (i.e., N ‐acetyl‐5‐methoxytryptamine), a molecule present in all organisms, is synthesized from the amino acid tryptophan in the pineal gland in animals . The role of melatonin in carcinogenic processes is being increasingly clarified; for instance, melatonin induces apoptosis in cancer cells, stimulates antioxidative enzyme expression, suppresses angiogenesis by inhibiting epidermal growth factor and vascular growth factor activities, and inhibits cell metastasis by regulating MMP‐9 expression and EMT . A recent study showed that disruption of the normal circadian melatonin signal promotes the cell growth and metabolism of breast cancer and induces chemotherapeutic resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin (i.e., N ‐acetyl‐5‐methoxytryptamine), a molecule present in all organisms, is synthesized from the amino acid tryptophan in the pineal gland in animals . The role of melatonin in carcinogenic processes is being increasingly clarified; for instance, melatonin induces apoptosis in cancer cells, stimulates antioxidative enzyme expression, suppresses angiogenesis by inhibiting epidermal growth factor and vascular growth factor activities, and inhibits cell metastasis by regulating MMP‐9 expression and EMT . A recent study showed that disruption of the normal circadian melatonin signal promotes the cell growth and metabolism of breast cancer and induces chemotherapeutic resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that melatonin has the potential of being used as a therapeutic agent for treating various types of human cancer, such as breast cancer , colon cancer , ovarian cancer , prostate cancer and lung cancer . Melatonin exhibits various pharmacological effects against cancer, including suppression of the expression of matrix metalloproteinases and inhibition of invasion and metastasis of cancer cells . Melatonin suppresses MMP‐9 transcription via modulating the expression of CREB‐binding protein (CREBBP) and E1A‐binding protein p300 (EP300), and decreasing histone acetylation , suggesting that histone acetylation plays important roles in melatonin‐related cancer treatment.…”
mentioning
confidence: 99%
“…According to the literature, this molecule regulates the proliferation of mammary tumor cells, angiogenesis-promoting proteins, and reduces breast cancer tumors in xenographic model (37)(38)(39). Melatonin also acts in metastatic control (22) and decreases the ability of tumor cells to invade and migrate (40).…”
Section: Discussionmentioning
confidence: 99%